2004
DOI: 10.1001/archinte.164.22.2409
|View full text |Cite
|
Sign up to set email alerts
|

Medical vs Surgical Management of Spinal Epidural Abscess

Abstract: Patients with spinal epidural abscess can be safely and effectively treated with conservative medical treatment without the need for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
1
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(118 citation statements)
references
References 16 publications
1
106
1
8
Order By: Relevance
“…Our rough estimate of the incidence of SEA at 1.8/100,000 persons per year accords with other published estimates [1,2], although its appearance after only 1.1% of the spinal operations performed by our neurosurgical service seems less frequent than others have reported [8]. We found that the commonest pathogen causing SEA was Staphylococcus aureus, just as in other reports [4,5,12,13,15,21,22]. SEA is usually associated with one or more comorbidities [7]; the list of our patients' comorbidities resembles the corresponding lists in other reported series [4,5,8,12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our rough estimate of the incidence of SEA at 1.8/100,000 persons per year accords with other published estimates [1,2], although its appearance after only 1.1% of the spinal operations performed by our neurosurgical service seems less frequent than others have reported [8]. We found that the commonest pathogen causing SEA was Staphylococcus aureus, just as in other reports [4,5,12,13,15,21,22]. SEA is usually associated with one or more comorbidities [7]; the list of our patients' comorbidities resembles the corresponding lists in other reported series [4,5,8,12].…”
Section: Discussionsupporting
confidence: 90%
“…Treatment and outcome SEA has occasionally been treated successfully with minimally invasive techniques [23,24] or with antibiotics alone [13,22,25], although the latter is considered controversial. Some of the patients reportedly cured in these ways had no neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Recent estimates are around 2-3 cases per 10,000 hospital admissions. 1,11,37,46 Spinal epidural abscesses can be classified into primary versus secondary. Secondary SEAs occur in patients with a history of invasive spinal procedures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…4,28 However, presentation is variable and can be ambiguous, leading to delayed diagnosis. 7,12,14,18,27,37,41 Reportedly, SEA usually occurs in the thoracolumbar spine, dorsally. 19,30,31 In one study, systemic symptoms were more common among those with ventral lesions, and focal deficits were more common among those with dorsal lesions.…”
Section: 10mentioning
confidence: 99%
See 1 more Smart Citation